Perbandingan Metode Weighted Product (WP) dan Simple Additive Weighting (SAW) terhadap Sistem Pendukung Keputusan Rekomendasi Calon Paskibraka - Riska Setiawati; Agung Triayudi; Ira Diana Sholihati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Paskibraka Selection is an activity held annually with the aim of finding the best boys and girls who will later be assigned to rise the duplicate heirloom flags in the Indonesian independence ceremony. In some areas, Paskibraka selection still uses excel calculations and other manual calculations. This manual calculation certainly takes longer and the results can be less accurate. Therefore, a decision support system application was made using the Weighted Product (WP) and Simple Additive Weighting (SAW) methods which can provide the final value of the selection assessment according to predetermined criteria and weights. The results of these two methods will be compared in order to get the best results. The results of this application are in the form of a ranking of participants based on their district.